Pengaruh Kualitas Pelayanan, Harga, Dan Kepercayaan Pelanggan Terhadap Kepuasan Pelanggan Pengguna Jasa Pada PT Detato Mitraindo Buana di Tangerang - Diah Rahmatika; Antoni Ludfi Arifin; Wahyuddin Latunreng (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2022)
The phenomenon of this research due to a decrease in the number of customers that occurred at PT Detato Mitraindo Buana, in order to survive and develop is to retain customers and increase the number of consumers by providing satisfaction to consumers. The purpose of this study is to determine and analyze impacts Service Quality, Price, and Customer Trust partially and simultaneously have on Customer Satisfaction. The research method used is quantitative analysis method, with a research sample of 50 respondents. Data was collected by using questionnaires and literature studies. Data analysis techniques used are: Validity Test, Reliability Test, Classic Assumption Test, Regression Analysis, Coefficient of Determination Analysis and Hypothesis Testing. The results showed that all independent variables partially have an positive and significant effect on customer satisfaction, with details: Service Quality (X1) of 28.8%, Price (X2) of 22.3%, Customer Trust (X3) of 24.3%. Simultaneously all independent variables have a positive and significant effect on customer satisfaction by 35.9%, the remaining 64.1% is influenced by other variables that are not included in this study.